Zooplankton composition and abundance in the Laptev Sea and adjacent Nansen Basin, summer, 1993 ... - Kireyev, Ivan (NSF Arctic Data Center, 2014)
Zooplankton composition and distribution were investigated on the Laptev Sea shelf, over the continental slope and in the adjacent deep Nansen Basin during the joint German-Russian expedition "Arctic 93'' with RV Polarstern and Ivan Kireyev in August/September 1993. Zooplankton was collected on four latitudinal transects (H, G, F and E) across the Laptev Sea continental shelf over the shelf break into the deep eastern Nansen Basin. Sampling was carried out between September 01 and 22, 1993 during the cruise "Arctic 93" with RV Polarstern (ARK IX/4). Five depth strata from the bottom or 1500 m to the surface were sampled in vertical hauls with a multiple opening-closing net (multinet, Hydrobios, Kiel, 0.25 m2 mouth opening, 150µm mesh) in the deep and slope zone. Regular depth intervals on the outer shelf and deep stations were 0-10-25-50-100-200 m and 0-25-50-200-500-1500 m (or bottom) respectively. In the shelf zone a Multinet with mesh size of 300 µm were used to sample the layers 0-10-20-30-40 m. The ...